Geração da base climática de Santa Maria – RS – para análise de desempenho térmico e eficiência energética de edificações - Flores, Michelle Gomes (2014)
The treatment and the availability of climatological data are essential to the buildings bioclimatic design. Energy efficiency can only be achieved when the plan considers local weather specificities. This study contributes with the subject through the systematization of climate data for the region of Santa Maria, RS. The data were collected to generate the Test Reference Year (TRY), the Typical Meteorological Year (TMY), the bioclimatic chart (via Analysis Bio and Psychros software), weather files compatible with programs such as EnergyPlus and Design Builder, the diagram of winds (wind rose) elaborated by the software Analysis SOL-AR and the typical day of project. Some of these systematizations already existed but they were related to a lower period of years. The study inputted hourly data of twelve years (2002 to 2013) and updated the data treatment methods. The files generation was based in a scientific bibliography and methodologies that have been employed by research groups concerned with the issue, such as works developed by Duffie and Beckmann (1980), Goulart (1993), Pereira (2004), Carlo and Lamberts (2005) and Roriz (2012). The results were conformed in a language accessible to designers and other agents in order to promote its effective use for better energy efficiency and comfort of building users in Santa Maria s region. Is was obtained 28,5% of comfort and 71,5% of discomfort. The ventilation is the main strategy for the summer, with 18,4%. For the cold, the solar heating, with 29,4%, is the best percentage. In relation to the summer winds direction, the predominant orientation is east. Therewith, the major importance of this research is in the knowledge of bioclimatic guidelines that help architects and engineers in architectonic propositions adjusted to the clime, besides the availability of climate files for thermo-energetic simulation.